Partial root-zone drying (PRD), its effects and agricultural significance: a review - Iqbal, Rashid (2022)
This review paper shows the consequences of partial root-zone drying happening on various plant species, its advantages and disadvantages, and also the hormone production under partial root-zone drying. In this technique of irrigation, a wet-dry cycle irrigates the crop, i.e., irrigation is scheduled at a regular interval with half way root drying.